Nasal delivery of Protollin-adjuvanted H5N1 vaccine induces enhanced systemic as well as mucosal immunity in mice. Issue 25 (5th June 2017) - Cao, Weiping; Kim, Jin Hyang; Reber, Adrian J.; Hoelscher, Mary; Belser, Jessica A.; Lu, Xiuhua; Katz, Jacqueline M.; Gangappa, Shivaprakash; Plante, Martin; Burt, David S.; Sambhara, Suryaprakash
Highlights: Protollin-adjuvanted H5N1 vaccine enhanced serum protective antibody responses and mucosal IgA responses. Protollin-adjuvanted H5N1 vaccine increased the early B cell response in the lymph nodes and spleen. Protollin-adjuvanted H5N1 vaccine increased the frequency of Ag-specific antibody secreting cells and T cells. Protollin-adjuvanted H5N1 vaccine conferred enhanced protection against viral challenge. Abstract: Sporadic, yet frequent human infections with avian H5N1 influenza A viruses continue to pose a potential pandemic threat. Poor immunogenicity of unadjuvanted H5N1 vaccines warrants developing novel adjuvants and formulations as well as alternate delivery systems to improve their immunogenicity and efficacy. Here, we show that Protollin, a nasal adjuvant composed of Neisseria meningitides outer membrane proteins non-covalently linked to Shigella flexneri 2a lipopolysaccharide, is a potent nasal adjuvant for an inactivated split virion H5N1 clade 1 A/Viet Nam1203/2004 (A/VN/1203/04) vaccine in a mouse model. Protollin-adjuvanted vaccines elicited enhanced serum protective hemagglutination inhibition titers, mucosal IgA responses, and H5N1-specific cell-mediated immunity that resulted in complete protection against a lethal challenge with a homologous virus as well as a heterologous clade 2 virus A/Indonesia/05/2005 (A/IN/05/05). Detailed analysis of adaptive immunity revealed that Protollin increased the frequency of lymphoid- as well as local tissue-resident antibody-secreting cells, local germinal center reaction of B cells, broad-spectrum of CD4 T cell response. Our findings suggest that nasal delivery of H5N1 vaccine with Protollin adjuvant can overcome the poor immunogenicity of H5N1 vaccines, induce both cellular and humoral immune responses, enhance protection against challenge with clade 1 and clade 2 H5N1 viruses and achieve significant antigen dose-sparing.